Conflictos competenciales: CCAA vs Estado, en materia de Ordenación del Territorio y Medio Ambiente. - Valle Pesquera, Gonzalo del; Alejandre Martín, Carlos; Béjar Padilla, Paula Belén; Bernabéu González, Francisco José; López-contreras González, Carmen (Observatorio Medioambiental, 1999)
Sin resumen